Dampak modernitas Budaya Ngopi Terhadap Pembangunan Ekonomi Lokal di Jember - Destri Aulia Wulandari; Nazala Zaikumar Elfa Rizqi; Netti Mahdalena Siregar (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2024)
This study discusses the impact of coffee culture modernity on local economic development in Jember district, East Java. Coffee culture has become an important part of the lives of the people of Jember, but modernity has changed the way people enjoy coffee and has had a significant impact on the local economy. The existence of modernity has made a shift in people in Jember who initially drank coffee at coffee shops, now they prefer to drink coffee in modern cafes that are more prestigious. This can of course threaten the existence of simple coffee shops, because the capital they have is not large, making it difficult for them to keep up with the development of modern society that continues to develop all the time. In this study, we use the concept of the juggernaut modernity theory by Anthony Giddens, where in his theory it is explained that modern life is an uncontrollable world, where there is always a process of change that occurs on a large scale and with a deeper scope. This study uses a qualitative research method with an ethnographic approach. The results of the study show that modernity has quite an impact on the economy of the local community, such as the increase in employment due to the number of modern cafes to the emergence of the threat of alienation received by simple coffee shops.